Emergency with Resiliency Equals Efficiency – Challenges of an EMT-3 in Nepal. Issue 6 (15th November 2018) - Yitzhak, Avraham; Merin, Ofer; Halevy, Jonathan; Tarif, Bader
Abstract: The 7.8 MW (moment magnitude scale) earthquake that hit Nepal on April 25, 2015 caused significant casualties and serious damage to infrastructure. The Israeli Emergency Medical Team (IEMT; later verified as EMT-3) was deployed 80 hours after the earthquake. A Forward Disaster Scout Team (FDST) that was dispatched to the disaster area a few hours after the disaster relayed pre-deployment information. The EMT staff was comprised of 42 physicians. A total of 1, 668 patients were treated. The number of non-trauma cases increased as the days went by. The hospitalization rate was 31%. Wound debridement procedures were the most common operations performed. A Yitzhak, O Merin, J Halevy, B Tarif .Emergency with resiliency equals efficiency- challenges of an EMT-3 in Nepal .Prehosp Disaster Med .2018 ;33 (6 ):673 –677 .